Colour Treatment of Aluminium Roof Sheets, a Significant Operating Factor - Kic, Pavel; Muller, Miroslav (Manufacturing Technology Journal, 2019)
Aluminium roofing is used for low weight, good strength and weather resistance, easy handling and assembly, for various roofs of industrial and agricultural buildings, residential and family houses, holiday homes, garages and various shelters. Important is very long life, relatively low price and the possibility to choose the colour design according to your taste. The basic form is a natural unpainted finish, which can be used because the aluminium roofing material is not subject to corrosion and is chemically stable. The aim of this research is to verify a suitable method of measuring the colour of aluminium roofing and to determine the basic characteristic values of the most common colours of aluminium roofing sheets. The identification by the CIELAB system makes it possible to characterize the suitability of roofing sheets in terms of reducing the heat gains of the roof structure, thus complementing this very practical information to the RAL colour marking system. This leads to a reduction of the cooling demand of air of the building in the summer. In terms of colour measurement and evaluation, the classical method according to the CIELAB system is where the colour attributes lightness (L-value), redness (a-value) and yellowness (b-value). These values may include the effect of surface gloss (SCI values) or exclusion (SCE values).
Keywords: Aluminium roof sheets; CIELAB; Colour measurement; Lightness; Surface roughness